Environnements naturel et matériel : vers une culture de l’éducation scientifique - Faouzia Kalali (Éducation et Socialisation)
The rapid changes and mutations that have accelerated over the past half century have led to an upheaval in contemporary socio-cultural realities. Natural and material environments become central to the issues where the new regime of knowledge about techno-science is linked far more than others have never been to the cultural, economic and political aspects of life in society. In this text we present how the breakthrough of this new regime has influenced scientific practices, these in turn influence the treatment of scientific issues at school.